2018
DOI: 10.1186/s12942-018-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the potential geographic accessibility from call to definitive care for patient with acute stroke

Abstract: BackgroundThe World Health Organization refers to stroke, the second most frequent cause of death in the world, in terms of pandemic. Present treatments are only effective within precise time windows. Only 10% of thrombolysis patients are eligible. Late assessment of the patient resulting from admission and lack of knowledge of the symptoms is the main explanation of lack of eligibility.MethodsThe aim is the measurement of the time of access to treatment facilities for stroke victims, using ambulances (firemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…Fourth, our analyses focused on driving times based on posted speed limits; however, actual driving speeds will be higher than posted ones for emergency vehicles and lower during difficult weather conditions or heavy traffic. 45 Not all people have access to vehicles, and use of driving time as a surrogate for access may overestimate access to care, especially in subgroups of people with lower car ownership. 46,47 True transit time includes not only driving time but also emergency medical services activation time, response time, on-scene time, and "door-in door-out" times for those seen first at a local hospital and subsequently transferred to a stroke center.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our analyses focused on driving times based on posted speed limits; however, actual driving speeds will be higher than posted ones for emergency vehicles and lower during difficult weather conditions or heavy traffic. 45 Not all people have access to vehicles, and use of driving time as a surrogate for access may overestimate access to care, especially in subgroups of people with lower car ownership. 46,47 True transit time includes not only driving time but also emergency medical services activation time, response time, on-scene time, and "door-in door-out" times for those seen first at a local hospital and subsequently transferred to a stroke center.…”
Section: Discussionmentioning
confidence: 99%
“…Park physical features may also play a vital role in encouraging park use or physical activity among residents [ 65 ], especially for specific features, e.g., playgrounds [ 66 ], water features [ 67 ] and vegetation [ 68 ]. In contrast, other features, such as litter, vandalism and poor playground surface quality have been shown to have a negative impact on park use [ 69 , 70 ].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The results indicated that moments when the adolescents are already engaging in technology-based activities to overcome boredom may be replaced with the active play of a mobile exergame. In addition, research shows that transportation stops or stations were often used by adolescents to wait for friends or public transportation [ 67 ]. Our study adds that during these timeframes, including waiting time and after-school hours, a mobile exergame may be interesting to play.…”
Section: Discussionmentioning
confidence: 99%